Antihypertensive Therapy and Cerebral Hemodynamics in Executive Mild Cognitive Impairment: Results of a Pilot Randomized Clinical Trial. Issue 2 (25th January 2013) - Hajjar, Ihab; Hart, Meaghan; Chen, Yu‐Ling; Mack, Wendy; Novak, Vera; C. Chui, Helena; Lipsitz, Lewis
<x xml:space="preserve">Abstract</x> Objectives To compare the effects of three antihypertensive medications on cerebral hemodynamic and cognitive function in hypertensive individuals with executive dysfunction. Design Double‐blind randomized clinical trial. Setting Community. Participants Fifty‐three individuals aged 60 and older with hypertension and executive dysfunction. Intervention Lisinopril, candesartan, or hydrochlorothiazide for 1 year. Measurements Cerebral blood flow velocity (BFV; transcranial Doppler ultrasonography during rest, sitting, standing, hypercapnia, and hypocapnia), cognition, and blood pressure were measured at baseline and after 6 and 12 months. Linear mixed models were used to compare the three groups. Results Of the 53 participants, 47 had successful insonation (mean age 72; 70% white; 57% women). There was a tendency toward an increase in BFV in the candesartan group and a decrease in the lisinopril and hydrochlorothiazide groups (between‐group P = .57) that was significant in those with low BFV at baseline (<median 27.6 cm/s, between‐group P = .03). The candesartan group also had the greatest improvement in executive function (Trail Making Test Part B improved by 17.1 seconds, vs hydrochlorothiazide improved by 4.2 seconds and lisinopril worsened by 14.4 seconds, P = .008). Carbon dioxide vasoreactivity and vasomotor range declined significantly in the lisinopril (within‐group P = .001 for vasoreactivity and .02 for vasomotor range) and hydrochlorothiazide groups (within‐group P = .10 and .009, respectively) but not in the candesartan group (within‐group P = .25 and .38, respectively; between‐group P = .30 and .46, respectively). Conclusion Angiotensin receptor blockers may preferentially preserve cerebral hemodynamics and executive function in individuals with executive dysfunction. These findings warrant further investigation in a larger trial.